Corporate social responsibility and employer attractiveness: a cross-country analysis of Northern and Southern European job seekers and young professionals - Minet, Nadine (2018)
This research paper focuses on the controversy whether corporate social responsibility (CSR) has an influence on employer attractiveness and to what extent the cultural background and individual character traits can act as influencing factors in this relationship. In a first survey a sample of 97 respondents have been asked about their general perceptions towards CSR and their employer choices. A second survey covered 109 participants in an experimental design, testing for statistical significance of CSR practices when choosing an employer. Finally, it can be concluded that CSR can have a significant influence on employer attractiveness in northern and southern Europe and individual character traits can provide an influential factor on the perception on CSR.